Development of a Noval Ultra-small Biomass Gasification and Power Generation System. (December 2017) - Lu, Ding; Yoshikawa, Kunio; Fukuhara, Minoru; Xin, Dai; Muhan, Li
Abstract: Small-scale, distributed and low cost biomass power generation technologies are highly required in the modern society. There are big needs for these technologies in the disaster areas of developed countries and un-electrified rural areas of developing countries. This work aims to demonstrate the technical feasibility of a portable ultra-small power generation system based on the gasification of carbonized wood pellet/briquette. A combined pretreatment process including carbonization and densification were adopted to deal with various biomass materials. Pelletization/Briquetting of carbonized fuel realized the stable operation of an updraft gasifier. After purification with several secondary clean devices, tar content in syngas was reduced to 0.49 g·m -3 and 1.4 g·m -3 for carbonized pellet and carbonized briquette, respectively. The cold gas efficiency during carbonized wood briquette gasification was about 64.4%, and the corresponding overall efficiency of the engine was 19.0%. Moreover, the steady output of 25 kW power was continuously realized. Therefore, the comprehensive system covering biomass carbonization, densification, gasification, syngas purification, and engine system is feasible for portable, ultra-small power generation